'Runaway' foreign film productions from a global South perspective: film workers' memories and site-specific traces from Thailand. Issue 3 (2nd September 2022) - Promkhuntong, Wikanda
ABSTRACT: This article explores the subject known in the Anglophone context as 'runaway' film productions through examining records by peripheral film workers and the legacy associated with a specific film location in Thailand. Considering the post-Cold War period when 'foreign' filmmaking had just taken off and the more recent (post)-COVID-19 labour movement within the country, the article proposes a revisit to film production history via a consideration of on-the-fringe paratexts, sporadically circulated in the public domain, as a way to explore discourses associated with this kind of transnational film productions. The article draws on two key written records associated with the making of The Killing Fields (1984) namely a set diary by the late Sompol Sungkawess, a writer/translator who worked as a local assistant director for the film; and a published monologue by the late Spalding Gray, a playwright/performer who took a minor role in the movie. By conducting a 'palimpsestuous reading' of these accounts along with various site-specific traces, the article explores past and present conditions and practices with the aim to project alternative imaginaries of transnational screen service industry from a global South standpoint.